Tbfmoc Methioine: Its Synthesis and Application for the Solid Phase Synthesis and Purification of Ubiquitin C-Hydrazide - Liu, Q.; Jin, Z.; Hu, N.F.; Wang, P. (Asian Journal of Chemistry, 2012)
The new reagent Tbfmoc-Met-OH is synthesized and used as a building block to replace Fmoc-Met-OH for the solid phase synthesis of ubiquitin C-hydrazide, an unnatural protein containing 76 amino acids and bring the Tbfmoc group into the synthetic product efficiently. The attached Tbfmoc group can provide good help for the product separation and improve the purification efficiency significantly.